Kompetensi Pedagogik Guru Bahasa Arab Dalam Merancang dan Melaksanakan Ealuasi Pembelajaran di Madrasah Aliyah Negeri (MAN) Yogyakarta - Cahya Edi Setyawan (At-Ta'dib, 2017)
Teachers should have good Pedagogic competence such as designing and implementing learning evaluation, including for Arabic language teacher. This competence will give an implications for improving students' learning outcomes. But in fact, the results of final examination for (Madrasah Ujian Akhir Madrasah Berstandar Nasional), the average score of Arabic from 2012 to 2016 is still relatively low (at 4.64). This study aims to determine the pedagogic competence of Arabic language as one of subject among teachers of Madrasah Aliyah Negeri (MAN) in designing and implementing learning evaluation in Yogyakarta. This research uses a quantitative approach with statistical analysis. Data collection techniques using test methods, and documentation. Data analysis used descriptive statistics that are converted by Five Points Benchmark Reference Assessment. All testing was done with SPSS 16 for windows. The results of this study indicate that the highest score is 97, the lowest score is 13, while the mean is 64.73 and the standard deviation is 17.68. Based on the five-level of PAP, the results showed that the level of pedagogic competence among  Arabic  Teachers of MAN in Yogyakarta in designing and implementing evaluation learning  is quite sufficient. This is evidenced by the average score is above 65. From this research, it is expected to be an evaluation and suggestion for Arabic teachers to be more active in improving pedagogic competence in designing and implementing learning evaluation.